South Africa's COVID-19 lockdown dilemma. Issue 3 (25th July 2020) - Ward, Michael
Abstract : Learning outcomes: The case presents a significant amount of information on the outbreak of COVID-19 and the expected impact on the economy. Although the case is necessarily concise, several links are given to the online articles and video material on which the case is based. This allows participants to deepen their knowledge of the virus and their understanding of its likely economic impact. To frame the discussion, several philosophies, ranging from Libertarianism to Marxism, are lightly expounded. Readers will need to consider divergent ideas; the sanctity of human life versus the monetary value of a life; the hysteria evoked by COVID-19 deaths versus the placid acceptance of an annual 66, 000 deaths by another disease – TB; and the differential economic impact of the virus across extremes of inequality. Perhaps, the key issue relates to the skewness in the death rate: Should young people's livelihood be sacrificed for a few old people about to die anyway? The case also illustrates the essence of a dilemma – a situation in which a difficult choice has to be made between two or more alternatives, especially ones that are equally undesirable. Case overview/synopsis: In March 2020, South African President Cyril Ramaposa ordered a 21-day national "lockdown" to enable and enforce social distancing in an effort to slow the spread of the COVID-19. Many other countries had already taken similar steps, but in a country with 43, 000 murders annually, South Africa's response to only 11 COVID-19 deaths and 1, 071 cases was both rapid and harsh. Schools, businesses, social areas and parks were closed. Medical emergencies, essential services and weekly grocery shopping were the only permissible activities. Two weeks after lockdown, there were 1, 845 cases and 18 deaths, a far cry from the predicted 30, 000 cases and 300 deaths, estimated on the basis of the three-day doubling rate at the start of lockdown. Many businesses, pulverised by closure, daily wage earners and those fearful of losing jobs were hopeful that the lockdown would not be extended. In a country with immense inequality, how would the masses under the age of 65 years, already in poverty and now with their lives pulled apart by an imported disease of the wealthy, respond to extended social and economic deprivation followed by bailouts for business? Complexity academic level: MBA and Executive Education Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS: 11 Strategy.